Extramedullary Plasmacytoma of the Larynx Treated by a Surgical Endoscopic Approach and Radiotherapy - Massimiliano Pino; Filippo Farri; Pietro Garofalo; Fausto Taranto; Andrea Toso; Paolo Aluffi (Case Reports in Otolaryngology)
Extramedullary plasmacytoma (EMP) is a rare variant of plasma cell myeloma that affects soft tissues. The head and neck region are the most affected sites, although others have also been described. Herein we report an uncommon case of EMP of the larynx in a 65-year-old male who presented with a history of progressive dysphonia and hoarseness. Laryngeal fiberscopy evidenced a reddish pedicled voluminous mass in the left false cords and ventricle. Microscopic suspension laryngoscopy was performed under general anaesthesia and a 4 W Acublade CO2 Laser was used for transoral resection of the lesion. This was followed by adjuvant radiotherapy, with the widely recommended doses on the supraglottic region, to achieve better local control. Diagnosis of EMP is based on immunohistochemistry and the exclusion of systemic plasma cell proliferative disorders. Diagnosis of solitary EMP can be made only if studies for disseminated disease and X-ray and/or magnetic resonance imaging of the spine, pelvis, femurs, and humerus and bone marrow biopsy are negative. As there are no internationally established guidelines, treatment of EMP is mainly based on consensus of expert opinion.